Мнемонічні властивості жанру апокрифу (на тлі різнорівневого аналізу твору Лесі Українки «Прокляття Рахілі») - Левчук, Юлія Олександрівна; Levchuk, Yuliia O. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Стаття присвячена проблемі жанру у творчості Лесі Українки, зокрема, досліджується жанр апокрифу як один із найархаїчніших форм інтерпретації Святого Письма. Використовується мнемонічний підхід до аналізу твору, що має в своїй основі поняття «пам’яті жанру» М. Бахтіна та «колективної пам’яті» П. Рікера.

The article is devoted to the genre in the works of Lesia Ukrainka, in particular, investigate the genre of the apocrypha as one of the most archaic forms of interpretation of the Holy Scriptures. Use a cognitive approach to the analysis of the work, called a mnemonic, which was considered to recent obsolete. The theoretical basis of this approach is the theory of the «memory of the genre» by M. Bakhtin. In addition, from the point of view of modern philosophy, the concept of «collective memory» (P. Ricoeur) is considered as the main engine of artistic creation. The study made it possible to establish the main mnemonical (that is archaic, old, traditional) features of the apocrypha in the work of Lesia Ukrainka, and managed to find out the specifics of copyright apocryphal story writer. The use of formal and structural approaches of identifying the main binary opposition, thanks to which the text of the apocrypha of Lesia Ukrainka elected a new angle of vision Bible. This opposition implemented in two concepts - birth and death, and more precise formulation - death in exchange for birth.
The mnemonic properties of the genre of the apocrypha (in the background tiered analysis of the work of Lesia Ukrainka "Rachel's Curse")
Keywords: апокриф; apocrypha; Біблія; Bible; мнемонічні властивості; mnemonic properties; пам’ять жанру; the memory of the genre; колективна пам’ять; the collective memory